Biocompatible biodegradable polymeric antibacterial nanoparticles for enhancing the effects of a third‐generation cephalosporin against resistant bacteria. Issue 3 (March 2017) - Mushtaq, Sana; Khan, Jawad Akbar; Rabbani, Faiz; Latif, Usman; Arfan, Muhammad; Yameen, Muhammad Arfat
Abstract : Purpose. : In the present study, enhancement of the the antibacterial activity of ceftriaxone against Gram‐positive (meticillin‐resistant Staphylococcus aureus ; MRSA) and Gram‐negative ( Escherichia coli ) bacteria with a biodegradable polymer was attempted. Methodology. : MRSA and E. coli were collected and identified by biochemical and molecular tests. Blank and ceftriaxone‐loaded chitosan nanoparticles (CNPs) were prepared by the ionic gelation method. In vitro antibiotic‐susceptibility studies were performed by disc diffusion, agar well plate method, Etest and time‐kill assay. In vivo activity was assessed using the neutropenic mouse thigh model and cytotoxicity was estimated by MTT (methylthiazolyldiphenyl tetrazolium bromide) assay with the MCF‐7 cancer cell line. Results. : MRSA showed 97% and E. coli 83% resistance against ceftriaxone in the disc diffusion test. The isolates showing a ≥1024 mg l −1 MIC value for ceftriaxone were selected for further evaluation. In the agar well plate method, the mean zones of inhibition for blank and ceftriaxone‐loaded CNPs were 17 and 23 mm, respectively, for MRSA isolates and 15 and 25 mm, respectively, for E. coli isolates. In the time‐kill assay, ˜1 log10 to ˜2.5 log10 reduction in viability was seen with both isolates when treated with ceftriaxone‐loaded CNPs over 24 h. The in vivo studies also showed the enhanced antibacterial activity of ceftriaxone‐loaded CNPs, with a 41% reduction in MRSA and a 27% reduction in E. coli burden. A low cytotoxicity of blank and ceftriaxone‐loaded CNPs was seen, with a slight reduction in the percentage viability of cells from 87 to 83% and from 88 to 81%, respectively. Conclusion. : The synergistic effect of ceftriaxone‐loaded CNPs is a useful finding for the treatment of MRSA and E. coli infections.